Enhancing Students' Reading Comprehension Through the Use of SQ3R in Teaching Analytical Exposition Texts - Putriana Ellen Bintang Pratiwi (Universitas Negeri Surabaya, 2025)
The purpose of this research is to determine if students who implement the SQ3R (Survey, Question, Read, Recite, Review) and those who do not significantly vary in their reading comprehension text of analytical exposition texts. A quasi-experimental design and quantitative approach were used in this research. Eleventh-grade students ate a senior high school in Gresik were the participants. There were two groups: the control group did not use the SQ3R, while the experimental group did. Reading comprehension tests were used as pre- and post-test to gather data. The tests consist of 20 multiple-choice questions. Data analysis included scoring student’s correct answers, conducting normality test, homogeneity test, and performing hypothesis testing, which tested using SPSS 25. The results showed that the experimental group’s post-test mean score was 84.84 (SD=8.659), whereas the control group was 79.69 (SD=9.667). It is seen that the experimental mean score was higher than the mean score of the control group. The significance value of 0.028, which is lower than 0.05, showed a significant difference between the two groups. These results suggest that students’ reading comprehension is positively impacted by the SQ3R strategy. This strategy can be considered an effective alternative in reading instruction.